Cover Image, Volume 98, Issue 6. (25th March 2018) - Wang, Jian; Wang, Chang; Zhen, Shoumin; Li, Xiaohui; Yan, Yueming
Abstract : The cover image, by Jian Wang et al., is based on the Research Article Low‐molecular‐weight glutenin subunits from the 1U genome of Aegilops umbellulata confer superior dough rheological properties and improve breadmaking quality of bread wheat, DOI:10.1002/jsfa.8700 . Abstract : The cover image, by Jian Wang et al., is based on the Research Article Low‐molecular‐weight glutenin subunits from the 1U genome of Aegilops umbellulata confer superior dough rheological properties and improve breadmaking quality of bread wheat, DOI:10.1002/jsfa.8700 .